Experience Hawaii - Miner Murray, Meghan; Oshiro, Jackie; Sekula, Sarah ([Not Specific]: Lonely Planet, 2022)
Lonely Planet's Experience Hawaii is your guide to unforgettable experiences and local surprises. Stoll through Honolulu's Chinatown, hike the Kalalau Trail, and see the sunrise at Haleakala - all guided by local experts with fresh perspectives. Uncover Hawaii's best experiences and get away from the everyday!
Includes index.
Keywords: Hawaii -- Guidebooks